Evaluation of Long-Term Irradiation Field in Geological Disposal of High-Level Radioactive Wastes - Sawamura, H; Nishimura, K; Naito, M; Ohi, T; Ishihara, Y; Neyama, A (Journal of nuclear science and technology, 2000)
Vitrified high-level radioactive waste (HLW) is subject to alpha, beta, gamma and neutron irradiation as a result of radionuclidedecay. Radiation can cause chemical and physical effects on HLW geological disposal system, in particular, engineered barrier system (EBS) which consists of vitrified waste, overpack container and surrounded buffer material. Alpha and beta radiation can be shielded completely by the overpack as long as it retains its containment function. Gamma and neutron radiation, on the other hand, will penetrate the overpack, and then enter the buffer material and the host rock. To assess radiation effects within the EBS for long time, it is essential to evaluate the evolution of irradiation field, quantitatively. Thus, radiation transport calculations were done to obtain dose rate, irradiation dose and absorbed dose in the irradiation field. In these calculations, vitrified waste, overpack, buffer and host rock were modeled with a same concentric cylinder.